Gene expression under chronic heat stress in populations of the mustard hill coral (Porites astreoides) from different thermal environments. Issue 16 (30th July 2013) - Kenkel, C. D.; Meyer, E.; Matz, M. V.
Abstract Recent evidence suggests that corals can acclimatize or adapt to local stress factors through differential regulation of their gene expression. Profiling gene expression in corals from diverse environments can elucidate the physiological processes that may be responsible for maximizing coral fitness in their natural habitat and lead to a better understanding of the coral's capacity to survive the effects of global climate change. In an accompanying paper, we show that Porites astreoides from thermally different reef habitats exhibit distinct physiological responses when exposed to 6 weeks of chronic temperature stress in a common garden experiment. Here, we describe expression profiles obtained from the same corals for a panel of 9 previously reported and 10 novel candidate stress response genes identified in a pilot RNA‐Seq experiment. The strongest expression change was observed in a novel candidate gene potentially involved in calcification, SLC26, a member of the solute carrier family 26 anion exchangers, which was down‐regulated by 92‐fold in bleached corals relative to controls. The most notable signature of divergence between coral populations was constitutive up‐regulation of metabolic genes in corals from the warmer inshore location, including the gluconeogenesis enzymes pyruvate carboxylase and phosphoenolpyruvate carboxykinase and the lipid beta‐oxidation enzyme acyl‐CoA dehydrogenase. Our observations highlight several molecular pathways that were not previously implicated in the coral stress response and suggest that host management of energy budgets might play an adaptive role in holobiont thermotolerance.